In vitro growth analysis of zea mays l. Using silver nanoparticles - SRIRAM.T; PANDIDURAI.V (International Journal of Pharma and Bio Sciences, 2017)
Nanotechnology and Nanobiotechnology are the emerging fields which have tremendous potentials to renovate agriculture and allied fields. Nanotechnology in the field of agriculture focuses currently on target farming that involves the use of nanoparticles with unique properties to boost crop and livestock productivity. So far both positive and negative effects of nanoparticles on plants have been reported. The present study was carried out to investigate the in vitro growth of Zea mays L. using silver nanoparticles. The present study reveals that small concentration of silver nanoparticles increases the in vitro growth of Zea mays L. Among the different concentrations (20ppm, 40ppm, 60ppm) 40ppm concentration of silver nanoparticles possess significant increase in the growth of shoot and root of Zea mays L. Similarly 60ppm concentration of silver nanoparticles possessed increasing germination in both dry and fresh weight of seeds when compared to other concentrations of nanoparticles.